Validity of death certificate variables in cases of death from external causes, Brazil - Barros, Maria Dilma de A; Ximenes, Ricardo; Lima, Maria Luiza C de (Revista de Saúde Pública, 2002)
OBJECTIVE: To validate variables other than the basic cause of death on death certificates from external causes of residents younger than 20 years old living in Recife, Brazil, in 1995. METHODS: A survey of death records of the Institute of Forensic in Recife was carried out in order to validate death certificate variables included in official mortality registries. Agreement analysis was performed using Kappa indexes and sensitivity. As a result of the methodology used, the study data was considered to be more consistent and therefore regarded as standard. RESULTS: Those variables forensic specialists indicated as their direct responsibility showed an excellent (gender, age, and category of violence) and good (type of accident) agreement. However, there were significant discrepancies in those variables seen as either of indirect or no forensic responsibility, such as locality and area where death took place, medical care provided and accident location. CONCLUSIONS: Data reveal a dissociation between the reasons for including some variables in death certificates and the obtaining strategy and their social purpose.